MOLUSKA PADA HYDROID (Aglaophenia cupressina) DI PERAIRAN BARAT PULAU SILADEN MANADO SULAWESI UTARA - Kambey, Alex D (Sam Ratulangi University, 2011)
Mollusks are one of benthic organisms that live on the sea bottom, often on the roots, stems, and leaves of plants. Hydroids (Aglaophenia cupressina), one constituent of coral reef organisms in the waters of Siladen Island, Manado, North Sulawesi, which is also an organism that has stingy nematocysts for divers in the region where they live, is a habitat of mollusks. Hydroids sampling was done by Scuba diving at 5 different depths, reef-flat, 5 m, 10 m, 15 m, and 20 m, respectively. All mollusks specimens were taken to the laboratory for species identification. Results found three species of epibiont mollusks on the hydroids, in which the bigger the hydroid size the larger the volume, and higher number was found. This results from that the mollusks use the hydroids as a shelter from predator attacks, strong currents and waves, and food search.